Trabalho presente e saúde ausente: diferenças entre sexos em uma indústria calçadista - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Introduction: Presenteeism is related to the performance of work activities even under adverse health and well-being conditions. Absenteeism, voluntary or involuntary absences, short to long term, which increase costs and decrease productivity. Both are indicators of health and health system performance. Objective: To analyze the risk factors related to presenteeism and absenteeism in workers in the footwear industry according to gender. Methods: In this five-year study, carried out in seven production units of a footwear multinational in northeastern Brazil, 9016 cases of presenteeism and 9072 of absenteeism were analyzed. Presenteeism, which refers to the health complaints of workers without sick leave, and absenteeism, characterized by absences from work due to health problems, were assessed using the International Classification of Functioning, Disability and Health (ICF). Poisson regression models were used to estimate the risk of recurrence of complaints and lost workdays.. Results and discussion: Presenteeism: For men, complaints are associated with the sewing sector (96%) and mental functions (5 times). For women, the cutting, assembly and finishing sector (43%) and genitourinary and reproductive functions (40%). There was no difference between the work shifts evaluated for men; for women, this factor was not significant. For both sexes, the administration of muscle relaxants, anti-inflammatories and analgesics appears to be involved in higher risk estimates. As for seasonal aspects, the month of April was convergent for men and women and, from an annual perspective, there is a tendency for the risk of complaints to increase. Absenteeism: Quality control and multifunctional workers are at a higher risk of absenteeism. Mental functions appear to be equally affected (10 times) for men and women working in quality control. Workers in this sector are at twice the risk of sensory/pain and genitourinary/reproductive dysfunctions. Multifunctional workers present a greater risk of cardiovascular, respiratory, hematological, immunological, digestive, metabolic and endocrine dysfunctions. However, neuromusculoskeletal Movement has a higher risk (10 times) compared to other disorders. In addition, men are three times more likely to be absent from work due to other categories that do not fall under the ICF. Conclusion: In summary, this study highlighted that both men and women can be affected by presenteeism and absenteeism, but risk factors vary by gender and work sector. In addition, the bodily functions affected can also differ between men and women.
Keywords: Saúde Ocupacional; Ergonomia; Sexo; Doenças Profissionais; Industria Manufatureira; CNPQ::CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; ODS 3 – Saúde e bem-estar